A simple method to immunopurify erythropoiesis stimulating agents from urine, aiming to optimize erythropoietin screening by SAR‐PAGE. Issue 11 (30th December 2019) - Heiland, Carmel E.; Masquelier, Michèle; Bhuiyan, Hasanuzzaman; Ericsson, Magnus
Abstract: The efficiency of the immunopurification step of urinary erythropoietin (EPO) and recombinant forms is important for their optimal detection in antidoping screening. Previous investigations of immunopurification techniques have been done for immunomagnetic beads, EPO Purification Kit (EPK) columns (MAIIA Diagnostics), and enzyme‐linked immunosorbent assay (ELISA) microplates (Stemcell Technologies) conjugated/coated with anti‐EPO antibodies. In this study, a new immunopurification technique using anti‐EPO sepharose gel beads, developed by MAIIA Diagnostics, to simplify and minimize sample handling was evaluated. This EPO Purification Gel Kit (EPGK) was compared with our current routine EPK for limit of detection (LOD). Linearity, recovery, repeatability, sample incubation time, and sample volume were also evaluated for EPGK. The LODs and linearity for EPK and EPGK were comparable to each other and the recovery for BRP, NESP, CERA, and EPO‐Fc were within the range of other studies, and concentration of the sample eluate improved the recovery results. Little variation was seen within days, between days, and between operators. A 90 minute incubation of the sample with the sepharose gel beads is sufficient for most of the erythropoiesis stimulating agents (ESAs) tested, with 10 mL being an optimal sample volume for EPGK. The improved sample handling, higher sample throughput and the reduced working time demonstrate that the EPGK is a better alternative to the current MAIIA EPK immunopurification method for urine. The EPO Purification Gel Kit (from MAIIA Diagnostics) was evaluated and validated for immunopurification of endogenous erythropoietin and exogenous erythropoiesis stimulating agents from urine samples. The kit was a better alternative to that currently used (EPO Purification Kit) in many antidoping laboratories because it improves sample handling and increases sample throughput. Abstract : The EPO Purification Gel Kit (from MAIIA Diagnostics) was evaluated and validated for the immunopurifying of endogenous erythropoietin and exogenous erythropoiesis stimulating agents from urine samples. The kit was a better alternative to that currently used (EPO Purification Kit) in many anti‐doping laboratories because it improves sample handling and increases sample throughput.